2018
DOI: 10.7196/samj.2018.v108i5.12784
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of myocardial injury after non-cardiac surgery: Experience at Groote Schuur Hospital, Cape Town, South Africa

Abstract: Background. Myocardial injury after non-cardiac surgery (MINS) is a newly recognised entity identified as an independent risk factor associated with increased 30-day all-cause mortality. MINS increases the risk of death in the perioperative period by ~10-fold. More than 80% of patients with MINS are asymptomatic, so the majority of diagnoses are missed. Awareness of MINS is therefore important for perioperative physicians. Objectives. To investigate the incidence of MINS after elective elevated-risk non-cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…Therefore, knowing physiological changes and avoiding intraoperative hemodynamic instability can help decrease ICC. However, the findings of current study disagree with the findings of the studies reported in most central and eastern European countries, including the USA ( 28 , 29 ). In many central and eastern European countries, the mortality rates of geriatric patients have declined in those aged over 65 years.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, knowing physiological changes and avoiding intraoperative hemodynamic instability can help decrease ICC. However, the findings of current study disagree with the findings of the studies reported in most central and eastern European countries, including the USA ( 28 , 29 ). In many central and eastern European countries, the mortality rates of geriatric patients have declined in those aged over 65 years.…”
Section: Discussioncontrasting
confidence: 99%
“…[3] A recent study found that the incidence of MINS in a South African (SA) patient population was comparable with those of large international cohorts. [11] The 1 500 SA patients included in the VISION cohort also suggested findings that could be compared with those of other international cohorts, and showed no evidence of differences between clusters. [6,7] It is therefore reasonable to assume that the SA patient population has a similar risk for MINS and outcomes after MINS to that in the literature.…”
Section: Prognosis Of Surgical Patients With Minsmentioning
confidence: 64%
“…The incidence of MINS was reported to be 5-8%, making it a frequent complication (Botto et al, 2014, Coetzee et al, 2018 in the post-operative scenario, associated with a 4-time increase in mortality population (Devereaux et al, 2017). Due to this clinical significance, proper treatment and prophylaxis for MINS are necessary.…”
Section: Strengths and Future Perspectivementioning
confidence: 99%